Evaluación de Bacillus sp. antárticos en la biodegradación de polietileno PET - Álava Cevallos, Sállury Gema (2023)
The objective of this study was to evaluate the biodegradation of polyethylene terephthalate (PET) by means of Bacillus sp. isolated from Antarctica. This research was of an experimental type, scientific approach on a unifactorial Completely Random Block Design (RCBD) and three blocks (15, 30 and 45 days). As treatments, five strains of the genus Bacillus sp. (DEE-71, T-29, T-13, GA-52, T-21) and control. The main material was the PET sheets that were subjected to a treatment with the bacteria in an enriched and mineral medium under room temperature conditions of 20°C and at 180 rpm. The biodegradation was evaluated by means of the percentage of weight loss and observation by light microscopy for two months. In the same way, the data were taken to an analysis of variance (ANOVA) and Tukey's test with 95% confidence. The percentage of biodegradation of the PET that will continue after 45 days was 0.4000%; 0.4250%; 0.0750%; 0.3250%; 0.2750%; 0.0000%, respectively, for the above-mentioned strains and the control. Likewise, signs of biodegradation were verified in the PET samples, such as: deterioration, fissures and grooves. Finally, the results of the present study revealed changes in the polymeric structure through the biodegrading capacity of the bacteria.